Rapid Determination of Full and Empty Adeno-Associated Virus Capsid Ratio by Capillary Isoelectric Focusing - Li, Tingting; Gao, Tie; Chen, Hongxu; Pekker, Peter; Menyhart, Adrienn; Guttman, Andras (Current Molecular Medicine, 2020)
Adeno-associated virus (AAV) is one of the most promising gene transfer vector types featuring long-term gene expression and low toxicity. The lack of pathogenicity and the availability of many serotypes augmented the applicability of AAV virions in gene therapy applications. The recombinant AAV capsid includes the therapeutic protein-coding transgene as well as a promoter to initiate translation and a poly A sequence portion for stabilization. Current AAV manufacturing technologies, however, cannot guarantee the generation of only full capsids, i.e., including the entire required genome. Partially filled and empty capsids are also part of the product, decreasing in this way the efficacy and safety upon clinical translation. Therefore, rapid, accurate and QC friendly analysis of the full and empty capsid ratio is of high importance during AAV vector manufacturing and release testing. In this paper, an automated capillary isoelectric focusing technique is introduced, readily applicable in the biopharmaceutical industry for fast and efficient determination of the full and empty capsid ratio. The method also reveals information about the proportion of partially filled capsids. For higher resolution (<0.1 pI unit), mixtures of wide and narrow range ampholytes were utilized. The isoelectric point and peak area percentage reproducibility (RSD) of the mixed ampholyte assay were as low as 1.67% and 2.45 % , respectively, requiring only 65 nL of sample volume per injection.
Keywords: Transgene